Hypercapnia-Driven Skeletal Muscle Dysfunction in an Animal Model of Pulmonary Emphysema Suggests a Complex Phenotype - Balnis, Joseph; Lee, Chun Geun; Elias, Jack A.; Jaitovich, Ariel (Frontiers in Physiology, 2020)
Patients with acute and chronic pulmonary conditions such as chronic obstructive pulmonary disease (COPD) often develop skeletal muscle dysfunction, which is strongly and independently associated with poor outcomes including higher mortality. Some of these patients also develop chronic CO2 retention, or hypercapnia, which is also associated with worse prognosis. While muscle dysfunction in these settings involve reduction of muscle mass and disrupted fibers’ metabolism leading to suboptimal muscle work, mechanistic research in the field has been limited by the lack of adequate animal models. Over the last years, we have established a rodent model of COPD-induced skeletal muscle dysfunction that allowed a disaggregated interrogation of the cellular and physiological effects driven by COPD from the ones unique to hypercapnia. We found that while COPD and hypercapnia synergistically contribute to muscle atrophy, they are antagonistic processes regarding fibers respiratory capacity. We propose that AMP-activated protein kinase (AMPK) is a crucial regulator of CO2 signaling in hypercapnic muscles, which leads to both net protein catabolism and improved mitochondrial respiration to support a transition into a substrate-rich, fuel-efficient metabolic mode that allows muscle cells cope with the CO2 toxicity.